Photo‐Supercapacitors Based on Third‐Generation Solar Cells. Issue 15 (2nd July 2019) - Meng, Hongguang; Pang, Shuping; Cui, Guanglei
Abstract: Photopowered energy systems (PPESs), which simultaneously achieve power conversion and energy storage, are one of the most promising auxiliaries to fulfill the giant and diversified power demand in modern society. Devices with a low cost, wearable, compact structure and the potential to add a variety of features (such as photochromic, flexible, textile, and wearable) have received extensive research attention. Photo‐supercapacitors are becoming one of the most extensively researched PPESs due to their ease of fabrication, mitigation of solar irradiation discontinuities, and the promotion of renewable energy utilization, and these devices have been fabricated with different combinations of photovoltage devices and energy‐storage technologies. This review summarizes the development of photo‐supercapacitors that integrate third‐generation solar cells and supercapacitors, with a focus on materials alignment, performance, structure design, and application. Finally, current challenges, possible solutions, and future perspectives are discussed. Abstract : Multipurpose materials : Integrated devices with energy conversion and storage functions can perform multiple functions and promote the utilization of renewable energy. This review summarizes the development of photo‐supercapacitors, which are one of the most prevalent integrated systems, to provide insight into the design of configurations and alignment of materials.